Characteristics of UV-MicroO3 Reactor and Its Application to Microcystins Degradation during Surface Water Treatment. (11th August 2015) - Zhu, Guangcan; Lu, Xiwu; Yang, Zhonglian
Abstract : The UV-ozone (UV-O3 ) process is not widely applied in wastewater and potable water treatment partly for the relatively high cost since complicated UV radiation and ozone generating systems are utilized. The UV-microozone (UV-microO3 ), a new advanced process that can solve the abovementioned problems, was introduced in this study. The effects of air flux, air pressure, and air humidity on generation and concentration of O3 in UV-microO3 reactor were investigated. The utilization of this UV-microO3 reactor in microcystins (MCs) degradation was also carried out. Experimental results indicated that the optimum air flux in the reactor equipped with 37 mm diameter quartz tube was determined to be 18∼25 L/h for efficient O3 generation. The air pressure and humidity in UV-microO3 reactor should be low enough in order to get optimum O3 output. Moreover, microcystin-RR, YR, and LR (MC-RR, MC-YR, and MC-LR) could be degraded effectively by UV-microO3 process. The degradation of different MCs was characterized by first-order reaction kinetics. The pseudofirst-order kinetic constants for MC-RR, MC-YR, and MC-LR degradation were 0.0093, 0.0215, and 0.0286 min −1, respectively. Glucose had no influence on MC degradation through UV-microO3 . The UV-microO3 process is hence recommended as a suitable advanced treatment method for dissolved MCs degradation.